2015
DOI: 10.5194/piahs-368-156-2015
|View full text |Cite
|
Sign up to set email alerts
|

Physically-based distributed modelling of river runoff under changing climate conditions

Abstract: Physically-based distributed modelling under changing climatic conditions has been carried out for the Northern Dvina River basin using the ECOMAG (ECOlogical Model for Applied Geophysics). The parameters of the model have been adjusted through calibration against runoff hydrographs observed for the period [2000][2001][2002][2003][2004][2005][2006][2007][2008][2009]. Validation of the model has been performed for the period of [1970][1971][1972][1973][1974][1975][1976][1977][1978][1979][1980][1981][1982][1983]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 5 publications
0
9
0
2
Order By: Relevance
“…Nash and Sutcliffe (1970) efficiency, NSE, and bias evaluation criteria were adopted to summarize the goodness of fit of simulated and measured daily discharge series. As an example, the evaluation criteria calculated for the outlets of the Lena and Northern Dvina River basins and adopted from Motovilov and Gelfan (2013), Gusev et al (2011Gusev et al ( , 2015 and Krylenko et al (2014) are shown in Table 1. 1967-1985; 1991-1998 0.85 −0.6 …”
Section: Hydrological Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nash and Sutcliffe (1970) efficiency, NSE, and bias evaluation criteria were adopted to summarize the goodness of fit of simulated and measured daily discharge series. As an example, the evaluation criteria calculated for the outlets of the Lena and Northern Dvina River basins and adopted from Motovilov and Gelfan (2013), Gusev et al (2011Gusev et al ( , 2015 and Krylenko et al (2014) are shown in Table 1. 1967-1985; 1991-1998 0.85 −0.6 …”
Section: Hydrological Modelsmentioning
confidence: 99%
“…Both models were applied earlier for simulating runoff hydrographs based on multi-year hydrometeorological observations in the Lena and Northern Dvina River basins and demonstrated good performance of simulations (Motovilov and Gelfan, 2013;Gusev et al, 2011Gusev et al, , 2015Krylenko et al, 2014). Trial-and-error manual procedure and the shuffle complex evolution (SCE-UA) automatic algorithm were applied for calibration of ECOMAG and SWAP, respectively.…”
Section: Hydrological Modelsmentioning
confidence: 99%
“…Для расчёта расходов воды, поступающей на верхние границы гидродинамической модели, использовались модели ECOMAG и искусственных нейронных сетей. Модель формирования стока ECOMAG ранее успешно применялась для сценарных расчётов стока при изменении климата в бассейне р. Северная Двина [31]. В режиме оперативных расчётов модели STREAM 2D и ECOMAG начали применяться для узла слияния рек Сухоны и Юга в ходе разработки описываемой системы прогнозирования.…”
Section: зеленцов и дрunclassified
“…In the eastern part of the Baltic Sea Basin, the current changes in the hydrological regime observed within the Belorussian territory during the past decades (increase of winter and decrease of spring streamflow) are projected to continue for four major river basins of the country (Volchek et al, 2017). The estimates of projected runoff changes over the Russian Northwest show a considerable change of seasonal runoff dynamics for the Volga (Georgievskiy et al, 2018) and the Northern Dvina Basins (Krylenko et al, 2015).…”
Section: Introductionmentioning
confidence: 98%